Psychological health disorders in kindergarten (Journal of the College of Education for Women, 2019)
The goal of modern education is to achieve healthy growth of the individual andsociety Since childhood is one of the most serious developmental stages in the humanidentity, which is not limited to the threat to it stage the foundations of personal sound isplaced where the dimensions of the various components and based on the foregoing targetsCurrent Search: "Measuring the level of psychological health kindergartens"And it included a sample search on the kindergarten children in the province ofBaghdad and achieve the objectives of research have been prepared in scale mental health andconcluded the researcher through the search results that kindergarten children suffering fromdisorders in mental health, the researcher recommends the deployment of the cultural andhealth awareness through the media of the importance of safety of physical and mental healthof children Riyadh The researcher suggests the work of similar studies of the current study tothe study of mental health disorders among other categories of children.